1994
DOI: 10.2307/2137943
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Family Planning and Childhood Immunization Services in Togo

Abstract: Improvements in the constellation of services in the African context are largely addressed through attaining better measures of service integration, which can be achieved through improved referral across categories of health programs. The use of an unobtrusive referral message that linked family planning and the Expanded Program of Immunizations (EPI) services was tested in an operations research study in Togo. The introduction of the referral message was accompanied by an 18-percent increase in awareness of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 2 publications
3
62
0
Order By: Relevance
“…Similar to a Togolese study in which the majority of service providers positively viewed the impact of integrating family planning services to the routine expanded programme on immunisation [36], the operational managers in this study reported being satisfied with 16 of the 17 dimensions of quality of care in the ICDM model. However, this was less so for the patients who reported satisfaction with 14 of these dimensions of care.…”
Section: Discussionsupporting
confidence: 58%
“…Similar to a Togolese study in which the majority of service providers positively viewed the impact of integrating family planning services to the routine expanded programme on immunisation [36], the operational managers in this study reported being satisfied with 16 of the 17 dimensions of quality of care in the ICDM model. However, this was less so for the patients who reported satisfaction with 14 of these dimensions of care.…”
Section: Discussionsupporting
confidence: 58%
“…Interventions varied considerably in character and counseling intensity, and were not described consistently. Four studies conducted interventions at infant vaccination visits: 2 studies [20,23] involved family-planning counseling and referral to a family-planning clinic, 1 study [24] provided education on breastfeeding and family planning, and another study [25] included multidisciplinary care with a social worker, pediatrician, and nurse practitioner. Other studies tested multiple additional visits outside of routine infant care.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 3 mother–infant care integration studies that reported positive results [2325], 1 study [25] was of fair quality and 2 studies [23,24] were of poor quality. In a randomized controlled trial of postpartum adolescents [25], the intervention group that received an integrated multidisciplinary mother–infant care program had a significantly decreased repeat pregnancy rate at 18 months compared with a control group that received routine well-infant care (12% versus 28%; P =0.003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum women may not seek health services to space their next pregnancy, but are likely to seek routine immunization services for their children [89]. Women bringing their children to facilities according to the routine vaccination schedule have multiple contacts with health providers over the course of their first year postpartum, providing opportunity to introduce integrated messaging on a number of critical health issues, including family planning [210].…”
Section: Introductionmentioning
confidence: 99%